Towards a Holistic Approach to Healthy Diet: Evidence from Iranian Health Perception Study. - Jila Sadighi; Ali Montazeri; Katayoun Jahangiri (Tehran University of Medical Sciences, 2014)
The aim of present study was to investigate the relation between the perception of population on healthy diet and lifestyle related behaviors.As part of national study on Iranian Health Perception, a cross-sectional study was carried out in Iran, 2010. A multistage sampling approach was applied to include a representative sample of population aged between 18 and 65 in the study. To collect data a designed questionnaire was administered.In all 27,883 individuals (50.4% women, 48.8% men) were included in the study. The mean age of participants was 34.6 years (SD = 12.8) and most were married (61%). The findings indicated that Iranian population often pay attention to healthy diet (39.5%), never smoke (74.9%), sometimes were doing exercise (29.5%), felt happy to some extent (39.5%), often care about themselves (47.1%) and rated their health as good (54.5%). Further analysis of the data showed that increased paying attention to healthy diet was associated with reduced smoking, more exercise, more self-care and happiness, and a better self-rated health status.The findings suggest that a healthy diet and other determinants of lifestyle are very integrated into each other. The efforts for changing any components of lifestyle can potentially change all individual related lifestyle behaviors. Indeed, one of effective strategies in fostering healthy diet is fostering other healthy lifestyles. This holistic approach might help decision-makers to design appropriate interventions in order to influence diet behaviors of people.